GANGGUAN TIDUR DAN DAMPAKNYA TERHADAP KESEHATAN OTAK - Shinta Brisma; Dian Budianti Amalina (Nusantara Hasana Journal, 2026)
Sleep disorders are common health problems that can have significant effects on brain health. Conditions such as insomnia, obstructive sleep apnea, and circadian rhythm disorders are known to be associated with various neurological disorders. This article aims to further examine the relationship between sleep disorders and brain health, including the underlying biological mechanisms and their impact on cognitive function and neurological diseases. The method used in this study is a literature review by examining various relevant scientific sources. The results of the review indicate that sleep disturbances can affect brain function through several mechanisms, including disruption of memory consolidation processes, increased oxidative stress, inflammation, and impairment of metabolic waste clearance through the glymphatic system. In addition, sleep disorders are also associated with an increased risk of neurological diseases such as stroke, cognitive decline, and neurodegenerative disorders. In conclusion, poor sleep quality and the presence of sleep disorders can negatively affect brain health; therefore, maintaining healthy sleep patterns is important as a preventive effort against various neurological disorders.